Pain Sensation and Long-term Suffering due to Chronic Pain in Patients with Rheumatoid Arthritis: Mediating Role of Self-efficacy - Amin Nejati; Hasan Ahadi; Farahnaz Meschi; Mohammad reza Seirafi; Adis kraskian mojembari (Iranian Association of Health Education and Health Promotion, 2020)
Background and Objective: the purpose of this study is to investigate the mediating role of self-efficacy as a cognitive factor in the relationship between pain sensation and long-term suffering. Methods: This is a descriptive correlational study. The statistical population of the study included all patients with chronic pain with Rheumatoid Arthritis referring to  11clinics and private and governmental centers specialized in chronic pain in Tehran and Karaj in a specified time interval (Between  Nov2015 and May 2016). 399 patients(257 women and 142 men) were selected via accessible sampling. The sensory pain index of the McGill pain scale, the Pain Discomfort Scale (PDS) and the Pain Self-efficacy Questionnaire (PSEQ) were used to collect the data. Data were analyzed by structural equation modeling (SEM). Results: The results showed that pain sensation and Self-efficacy are considered as good predictors of long-term suffering. Based on the findings of the structural equation modeling, there are significant and a positive causal relationship between pain sensation, self-efficacy and long-term suffering and the mediating role of self-efficacy in the relationship between pain sensation and long-term suffering has been confirmed (P<0.05). Conclusion: The result of this research, In addition to conceiving long-term suffering, It can be helpful in identifying one of the cognitive-emotional factors of long-term suffering, providing more adaptive strategies for people with in prevention and treatment and health promotion.